Topkapı Sarayı Müzesi arşivi 34 numaralı Filori defteri : (değerlendirme-transkripsiyon) - Yiğit, Osman (My University, 2018)
Topkapı Sarayı Müzesi Arşivi’nde “TSMA. d. 00034” fon kodu ve “Filori Defteri” adıyla kayıtlı olan bu defter 978-1019/ 1570-1611 yılları arası harc-ı hassanın altın nev’inden olan kayıtlarını ihtiva etmektedir.

This register, which is recorded with the reference code “TSMA D. 0034” and named as “Florin Register”, contains the gold bonds of the imperial expenditures between 978-1019/ 1570-1611. 4 years of record belongs to Selim II, 21 years belongs to Murad III, 8 years belongs to Mehmed and 8 years belongs to Ahmed I’s reign.
Keywords: 18 yy; 18th century; 19 yy; 19th century; Budget; Bütçe; Ceyb-i Hümayun; Economic conditions; Ekonomik durum; Filori Defteri; Florin Registers; Harc-ı Hassa; History; Imperial Expenditures; İç Hazine; imperial coffers; inner treasury; Osmanlı İmparatorluğu, 1299-1918; Ottoman Empire, 1299-1918; Tarih; Turkey; Türkiye